The profile of bacteria isolated from urine culture of adults with urinary tract infection in Yogyakarta 2007-2022 - Aman, Abu Tholib; Nuryastuti, Titik; Aman, Alia Hanifa; Linda, Vitia Ajeng Nur; Mawarti, Yuli (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Local data regarding antimicrobial susceptibility patterns of bacteria from urine culture is limited in Indonesia, particularly in Yogyakarta. This study was conducted to provide epidemiology data of bacteria and their resistance profile, including the profile of bacteria that producing extended-spectrum beta-lactamase (ESBL) and carbapenemase in the urine of patients with urinary tract infection (UTI) in Yogyakarta. A descriptive retrospective study was conducted by assessing laboratory records of urine culture from adult patients at the Microbiology Laboratory, Department of Microbiology, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta between 2007 and 2022. Of the 842 urine cultures, 464 (55.11%) isolates were recovered. Among thisolates, 50 (10.78%) were fungi, 67 (14.44%) were Gram-positive bacteria, and 347 (74.78%) were Gram-negative bacteria. Enterococcus sp. (41 (61.19%)) was the most bacteria found in the Gram-positive bacteria group, while Escherichia coli (38.90%) were the most bacteria found in the Gram-negative bacteria group. This study also identified Gram-negative bacteria producing ESBL enzymes (58.70%) and carbapenemases (27.94%). Gram-negative bacteria are the most common bacteria found in urine cultures of adult UTI patients in Yogyakarta, and the resistance profile of these bacteria is concerning.